Incomplete pulmonary fissures evaluated by volumetric thin-section CT: semi-quantitative evaluation for small fissure gaps identification, description of prevalence and severity of fissural defects - Koenigkam-Santos, Marcel; Paula, Wagner Diniz de; Owsijewitsch, Michael; Wielpütz, Mark Oliver; Gompelmann, Daniela; Schlemmer, Heinz-Peter; Kauczor, Hans-Ulrich; Heußel, Claus Peter; Puderbach, Michael (European journal of radiology, 2013)
Objective - To assess the interobserver agreement for a semi-quantitative evaluation of the interlobar fissures integrity in volumetric thin-section CT images, looking for more detailed information regarding fissural defects; and describe prevalence and severity of fissural defects between the different functional groups of subjects. - Materials and methods - Volumetric scans of 247 individuals exposed to tobacco with different functional status (normal to severe COPD), were retrospectively and independently evaluated by 2 chest radiologists, with a consensual reading additionally with a third reader in disagreement cases. Right oblique (RO), right horizontal (RH) and left oblique fissures (LO) integrity was estimated using a 5% scale. GOLD classification was available for all subjects. - Results - Interobserver agreement (weighted Kappa-index) for fissural categorization was 0.76, 0.70 and 0.75, for RO, RH and LO, respectively. Final evaluation found 81%, 89% and 50% of RO, RH and LO to be incomplete, with respective mean integrity of 80%, 58% and 80%. Small fissure gaps (<10%) were present in 30% of patients. Prevalence and severity of fissural defects were not different between the GOLD categories. - Conclusions - A substantial agreement between readers was found in the analysis of interlobar fissures integrity. The semi-quantitative method allowed a detailed description of the fissural defects, information that can be important, for example, in endoscopic lung volume reduction therapies for emphysema. Small fissure gaps, overlooked in previous studies, were found in almost a third of the patients. A higher than previously described prevalence of fissural defects was described, but without significant differences among the distinct functional groups.
Gesehen am 30.03.2021